(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The mass transition of universities to online distancing education in recent times has caused a problem with this form of education. These are, in particular, questions about how to conduct lectures and classes, laboratory work, tests and how to get a connection from students. And, of course, one of the most important issues is objective examination and evaluation. This article discusses some ways to increase the objectivity of the assessment of the perceptions of university students on various issues in the course of various online distancing training.